Advances in 4D‐printed physiological monitoring sensors. Issue 3 (16th December 2021) - Mahmud, M. A. Parvez; Tat, Trinny; Xiao, Xiao; Adhikary, Partho; Chen, Jun
Abstract: Physiological monitoring sensors have been critical in diagnosing and improving the healthcare industry over the past 30 years, despite various limitations regarding providing differences in signal outputs in response to the changes in the user's body. Four‐dimensional (4D) printing has been established in less than a decade; therefore, it currently offers limited resources and knowledge. Still, the technique paves the way for novel platforms in today's ever‐growing technologies. This innovative paradigm of 4D printing physiological monitoring sensors aspires to provide real‐time and continuous diagnoses. In this perspective, we cover the advancements currently available in the 4D printing industry that has arisen in the last septennium, focusing on the overview of 4D printing, its history, and both wearable and implantable physiological sensing solutions. Finally, we explore the current challenges faced in this field, translational research, and its future prospects. All of these aims highlight key areas of attention that can be applied by future researchers to fully transform 4D printed physiological monitoring sensors into more viable medical products. Abstract : This perspective focuses on the overview of 4D printing, its history, and both wearable and implantable physiological sensing solutions. The current challenges faced in this field, translational research, and its future prospects are explored. All of these aims highlight key areas of attention that can be applied by future researchers to fully transform 4D printed physiological monitoring sensors into more viable medical products.